Experimental exploration on stable expansion phenomenon of sheath flow in viscous microfluidics - Zhao, Wenhan (2023)
Microfluidic technologies have been developed for decades, especially in bio-chemical research and applications. Among them, sheath flow is one of the most well-known techniques used for focusing microparticles into extremely narrow widths. With varying Reynolds numbers, sheath flow displays different behaviors, including diffusion, stable thread, and turbulence. In this study, a previously unknown phenomenon, namely, stable expansion, is originally reported in a 200 × 70 μm microchannel with a Reynolds number ranging from ∼10 to ∼110. This stable expansion of focusing width differs from all the reported phenomena in the literature and is experimentally explored in this study. First, the phenomenon is introduced, identified, and comprehensively described using different experimental samples and methods. Subsequently, an image processing algorithm of post-analysis is proposed and calibrated by the theoretical results of stable thread. Based on the calibrated standard protocol, the effects of flow rates and a hysteresis phenomenon due to variation in the flow rate are revealed and studied. In addition, the effects of fluid viscosity are investigated by introducing a mixture of deionized (DI) water and glycerin. It is found that, in this 200 × 70 μm2 (weight × height) microchannel made of PDMS, the stable expansion phenomenon will occur when the Reynolds number exceeds 10, and the expanded width will increase with total flow rate. Moreover, it is found that the expanded width in a flow rate reducing route is displayed to be wider than that in an increasing route. On the other hand, a high viscosity contrast (>40) between the middle sample and sheath flows can eliminate the focusing width expansion. The results indicate that this originally revealed phenomenon is experimentally repeatable and worth further studying to help researchers better understand the mechanism of microfluidics.